Effectiveness of Prenatal Yoga on Pregnancy Discomfort in Pregnant Women in the II and III Terms - Nujulah, Lailatul (Universitas Muhammadiyah Sidoarjo, 2025)
Pregnancy often leads to physical and psychological changes that can cause significant discomfort for expectant mothers. While such discomforts are generally physiological, they require attention to prevent negative effects on both maternal and fetal health. Prenatal yoga is a non-pharmacological intervention that may help alleviate these discomforts and support a smoother labor process. This study aims to evaluate the effectiveness of prenatal yoga in reducing discomfort levels among pregnant women in their second and third trimesters. A quasi-experimental design with a one-group pre-test post-test approach was used. The study involved 30 pregnant women in their second and third trimesters, selected through purposive sampling. Participants attended prenatal yoga sessions four times per week, with each session lasting 60 minutes. Data were collected using the Numeric Rating Scale (NRS) for back pain and leg cramps, the Pittsburgh Sleep Quality Index (PSQI) for sleep quality, and the Hamilton Rating Scale for Anxiety (HRS-A) to assess anxiety levels. Data analysis was conducted using the Wilcoxon test, with a significance threshold of p < 0.05. The results showed a p-value of 0.000 for all measured variables—indicating significant improvements in back pain, leg cramps, sleep quality, and anxiety levels after the yoga intervention. These findings suggest that prenatal yoga is effective in reducing both physical and psychological discomforts during pregnancy. It can be considered a beneficial, low-risk strategy to enhance maternal well-being in the later stages of pregnancy.